OBSTACLES TO THE PROCESS OF SEXUAL VIOLENCE LAW ENFORCEMENT IN ACEH UTARA - Zulkifli; Arief Rahman; Martina (CV. RADJA PUBLIKA, 2023)
Aceh Province as recorded by the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) Aceh, although there are still 697 cases of sexual violence against women from January to September 2021. The legal basis used in the law enforcement process of sexual violence against women in North Aceh is Aceh Qanun No. 6 of 2014 concerning Jinayat Law, but in its implementation there are various obstacles faced. The study aims to identify obstacles to the law enforcement process of sexual violence against women in North Aceh. Respondents in the study amounted to 21 people selected by accidental sampling. The types of data in the form of primary data and secondary data were analyzed descriptively qualitatively. The results of the study explainthat there are obstacles in law enforcement of sexual violence against women in North Aceh District among the legal obstacles, namelyThe District Court is not authorized to hear cases of rape because the case should have referred to the qanun jinayat instead of the Child Protection Law. Law enforcement constraints are communication barriers between law enforcers and victims who do not understand the use of Indonesian, especially children, facilities and facilities constraints which include lack of consequences of budget and lack of shelter as well as the high cost of visas, and societal and cultural constraints that includethe families of the victims are reluctant to report cases of sexual violence because they consider this incident to be a disgrace and must be covered up. In the end, some of the case investigations stopped in the middle of the road.